Distribución de dos especies de orquídeas huntleya meleagris lindl y psychopsis krameriana (rchb.f) h.g. Jones, según el grado de intervención de la vegetación en la zona de amortiguamiento de la reserva ecológica cofán bermejo, en la parroquia el dorado de Cascales, cantón Cascales, provincia de Sucumbíos - Cambizaca Pelaez, Jessica Lorena (2016)
The purpose of the investigation was to determine the distribution of orchids Huntleya meleagris Lindl y Psychopsis krameriana (Rchb.f) H.G. Jones, two types of ecosystems according to the degree of intervention, was made 12 transects in secondary forest and 12 transects in succession forest of 50x10m, identifying the species of orchid, the host tree, number of orchids by host tree and orchid high in the host tree. We identified 303 individuals of orchids Huntleya meleagris Lindl and Psychopsis krameriana (Rchb.f) H.G. Jones identified in secondary forest, while succession forest 59 orchids were identified, with the result that there is greater distribution in secondary forest. Was calculated Density, relative density, relative frequency, importance value index was calculated and concluded that the two species of orchids study Huntleya meleagris Lindl orchid has greater ecological value in both types of ecosystems with an IVI of 53.31% while Psychopsis krameriana (Rchb.f) H.G. Jones with an IVI of 35.09%. Orchids inventory conducted in both types of ecosystems the Shannon diversity index (H ') and Simpson dominance index (δ) was determined with what conclusion was reached that orchids Huntleya meleagris Lindl and Psychopsis krameriana (Rchb. f) H.G. Jones are highly diverse, compared to other orchids inventoried in the study area.